The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/jonm.12682
|View full text |Cite
|
Sign up to set email alerts
|

Work pattern of neurology nurses in a Chinese hospital: A time and motion study

Abstract: Aim To investigate nursing work patterns in a neurology department in a Chinese hospital. Background Knowledge of nursing work patterns is important for nursing management and work design, and for the evaluation of organizational process change associated with the introduction of an innovation. Methods A time‐and‐motion method was used to observe 14 registered nurses’ (RNs’) work patterns in a neurology department in a Chinese hospital. Results There were 147 hr of observation. Overall, the most time‐consuming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 26 publications
3
17
1
Order By: Relevance
“…Most time and motion studies collect data for short blocks of time which may lead to an under or over representation of certain tasks. Only Yu et al, (2019) collected data on the work pattern of nurses for entire shifts reporting that documentation took up 28.3% It is evident from the literature that there is a need to measure nurses and midwives perception of the burden of documentation with a valid and reliable tool. Such a tool will provide information on how documentation has an impact on nurses and midwives workload and how they perceive it influences the care they provide to patients.…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 4 more Smart Citations
“…Most time and motion studies collect data for short blocks of time which may lead to an under or over representation of certain tasks. Only Yu et al, (2019) collected data on the work pattern of nurses for entire shifts reporting that documentation took up 28.3% It is evident from the literature that there is a need to measure nurses and midwives perception of the burden of documentation with a valid and reliable tool. Such a tool will provide information on how documentation has an impact on nurses and midwives workload and how they perceive it influences the care they provide to patients.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Time and motion studies exploring the work patterns of clinical nurses have included measures of time spent on clinical documentation (Antinaho, Kivinen, Turunen, & Partanen, ; Ballermann, Shaw, Mayes, Gibney, & Westbrook, ; Hendrich, Chow, Skierczynski, & Lu, ; Westbrook, Duffield, Li, & Creswick, ; Yen et al, ; Yu et al, ). There is considerable variation in the amount of time these studies have reported nurses spend on documentation from as low as 7.3% (Westbrook et al, ) to as high as 28.3% (Yu et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations